[Epsilon]-Glycation, APP and Aβ in ageing and Alzheimer disease: a hypothesis - Schmitt, Horst Peter (Medical hypotheses, 2006)
Summary: The post-translational modifications of protein molecules include glycation, which may not only occur enzymatically controlled in N and O position, but also wherever proteins meet reducing sugars non-enzymatically in ε position at lysines (non-enzymatic (ε) glycation (NEG)). The formation of keto-amines from the amine-sugar compounds (Amadori re-arrangement) and further processing of the largely undigestible Amadori compounds eventually results in insoluble advanced glycation end products (AGEs). The latter can induce or favour disease including mental disorders. Preferential targets of NEG include large cell surface proteins. Ample evidence has been provided that NEG also occurs in the brain where cross-linking of ε-glycated proteins, induction of oxidative stress and signalling of AGEs through their specific receptor (RAGE) likely play a role in (brain) ageing and Alzheimer disease (AD). This is underscored by the demonstration of particular interactions between AGE/RAGE and amyloid-β (Aβ) that favour the aggregation and deposition of Aβ and, perhaps, the formation of Aβ itself. The close relationship between NEG and Aβ, as well as other facts foster the hypothesis that NEG of the large trans-membrane amyloid precursor protein (APP) might be a significant factor in the induction of aberrant APP cleavage with production of Aβ, not only in normal ageing, but also in AD. Blockade of lysine cleavage sites on APP by sugar chains or marker effects induced by NEG akin to ubiquitination of proteins for degradation at lysines could be expected to contribute to altered processing of APP. The hypothesis of ε-glycation in APP proposed here and the review of evidences for the significance of NEG in brain ageing and AD are aimed at the stimulation of investigations into the still open question which role NEG plays with respect to APP and its abnormal processing in AD. It can be rendered likely that such research might open new avenues towards decreasing the risk of AD and/or slowing its progression through the prevention of NEG in APP with aberrant APP processing, increased generation of Aβ and the formation of AGEs from ε-glycated APP.